Upaya Pembuktian Melalui Saksi Dalam Penuntutan Tindak Pidana Penganiayaan Yang Menyebabkan Luka Berat (Studi Kasus di Kejaksaaan Negeri Surakarta) - Christanti, Nia Yunita; , Hartanto S.H.,M.Hum (2016)
The purpose of this study was to analyze the efforts to prove through witness testimony in the prosecution of criminal acts of persecution that led to serious injuries, the barriers faced by the Prosecutor in efforts to prove the criminal acts of persecution that caused serious injury, as well as efforts to overcome these obstacles. This research includes empirical legal research. Research conducted at the State Attorney Surakarta. The data source using primary data. Data were analyzed using qualitative analysis. The results showed that: efforts prosecutor in the prosecution of criminal acts of persecution that caused severe injuries is to provide a layered indictment is the primary charge and subsaider, propose witnesses against him (a charge). In order for the witness testimony is considered valid by the judge must be given under oath, given in front of the court, and only provide information of value as evidence. The obstacles faced by the prosecutor in efforts to prove through witness testimony in the criminal acts of persecution that causes serious injury is the lack of participation of witnesses in the trial, witness testimony does not correspond to other witness testimony, and witnesses retract statements in the dossier. Efforts to overcome obstacles prosecutor is asking the judge to forcibly bring the witness in the trial, asking the judge's role to seek the material truth, and use witness testimony in court as evidence.